40 years of continuous renal replacement therapy - Bellomo, Rinaldo 1956-; Kellum, John A.; La Manna, Gaetano 1962-; Ronco, Claudio 1951- (Contributions to nephrology / series editor Claudio Ronco, 2018)
Continuous renal replacement therapies (CRRT) started off as an alternative to hemo- or peritoneal dialysis. Today's machines and techniques are the result of 4 decades of developments, studies, and practices which can be divided into 4 distinct stages: exploration and development; birth of a new specialty called critical care nephrology; design of specific new devices and machines; and interaction among various specialists to adapt extracorporeal therapies for multiple organ support and sepsis. This book features contributions from prominent CRRT experts from around the world. It is an important tool for educating a new generation of nephrologists and intensivists. At the same time, it provides the most advanced CRRT users with the latest technological information, the most updated clinical evidence, and the personal opinion of key leaders who contributed to the last 40 years of history in the field.